Perlindungan Hukum Atas Pemutusan Hubungan Kerja Pada PT Halit International; Analisis Putusan Mahkamah Agung Nomor 971 K/P3DT. Sus-PHI/2018 - Iis Apriyani; Indra Rahmatullah (JOURNAL of LEGAL RESEARCH, 2019)
AbstractThis research was conducted because of the varied object of the decision related to the fulfillment of the rights of workers who were dismissed from work, causing legal uncertainty regarding procedures and fulfillment of workers' normative rights. Like one of the cases of PT. Hollit International, who in the first instance verdict of the panel of judges rejected the claim of all workers' rights, but at the cassation level, the panel of judges overturned the first instance because the Industrial Relations Court at the Central Jakarta District Court had incorrectly applied the law. This research uses qualitative research that is the type of data and analysis that is used is narrative, in the form of statements that use reasoning. By using a normative juridical approach, referring to the application of the law contained in a decision and the law which is conceptualized as a norm or norm that applies in society. The results of the research show that the court's decision on the claim of workers 'rights which is dismissed by the company is not comprehensive and is not synchronous between the Labor Law and the Decision in the Industrial Relations Court, causing legal uncertainty in the process of fulfilling workers' rights.Keywords: Rights, Labor, Mutation, Termination of Employment